PERFORMANCE OF A TANGENTIALLY FIRED BOILER IN A THERMAL POWER PLANT - Abhinash, Koilada; Kishore, P.S. (International Journal of Research -GRANTHAALAYAH, 2018)
The most effective method for producing intense turbulence is by the impingement of one flame on another. This action is secured through the use of burners located in each of the four corners of the furnace. The burner nozzles are so directed that the streams of coal and air are projected along a line tangent to a small circle, lying in a horizontal plane, at the centre of the furnace. A scrubbing action is present which assures contact between the combustible and oxygen, thus promoting rapid combustion and reducing carbon loss. The experimental results of this study can be summarized as the use of tangentially fired boiler which increase splendid air-fuel mixture and pulverized coal is entrained in Primary Air (PA), and in-addition to that the Secondary Air (SA) is also projected towards the mill, finally a rotating “FIRE BALL” is formed. The present work analysis is carried out on Tangentially Fired Boiler by considering heat input through four burners. The heat output is determined by considering various losses from the boiler that is loss due to dry gas, loss due to moisture, loss due to H2 for combustion, heat loss due to combustile and refuse and losses due to radiation etc. In addition heat absorbed by economizer, boilers, superheater and reheater are studied, thus finally the net heat absorbed and thermal efficiency of tangentially fired boiler are determined. Graphs are drawn to evaluate the various effects of heat input on output parameters in the boiler. Sankey diagrams are drawn to show the performance in the boiler. The values calculated are put and shown as tables in Appendix.